(untitled) (Palaeohispanica. Revista sobre lenguas y culturas de la Hispania Antigua, 2020)
The corpus of Cisalpine Celtic inscriptions consists of c. 430 short texts (graffiti and engravings) in two different Ancient Celtic languages, Lepontic and Cisalpine Gaulish. The inscriptions, which are mostly written in a variant of the North Italic script, date approximately from the 7th to the 1st centuries BC and are confined to a small area around the North Italian lakes and the Po Valley. This article presents the current knowledge about the Cisalpine Celtic corpus and indicates directions of future research.